Pelindungan Hak Asasi Manusia Dalam Konflik Bersenjata Non Internasional Di Myanmar - Hayer, Karel Neju; Wattimena, Josina Augustina Yvonne; Leatemia, Wilshen (Faculty of Law Universitas Pattimura, 2024)
ABSTRACT: A non-international armed conflict occurred in Myanmar as a result of a military coup which triggered a wave of protests and demonstrations. Human rights violations occurred by the Myanmar military and ethnic armed groups, including mass killings, rape and sexual violence. The aim of this research is to examine and understand human rights violations committed by parties involved in the non-international armed conflict in Myanmar, to examine and determine the obstacles faced in protecting human rights in Myanmar during the non-international armed conflict. The research method used is Normative Juridical research. The problem approaches used are the statutory approach, concept approach and case approach. Sources of legal materials used are primary, secondary and tertiary legal materials. procedures for collecting legal materials and processing analyzes of prescriptive legal materials through methods of interpretation, harmonization, systematicity, and legal discovery. The research results show that in the non-international armed conflict in Myanmar, a series of serious human rights violations occurred. This includes the use of force against civilian demonstrators, arbitrary arrests, and repression of pro-democracy activists. In addition, there were reports of acts of torture and sexual violence. There are a number of obstacles in protecting human rights in Myanmar during non-international armed conflicts.